A143 ENTEROID CELL DIFFERENTIATION IS UNDER class I HDAC CONTROL. (15th March 2019) - Gonneaud, A; Turgeon, N; Jones, C; Boisvert, F; Boudreau, F; Asselin, C
Abstract: Background: Introduction: Deacetylases HDAC1 and HDAC2 are epigenetic erasers of acetyl marks on histones and transcription factors, among others, and thus regulate gene expression, cell proliferation and differentiation. We have shown that, in contrast to subtle defects upon Hdac1 or Hdac2 specific IEC-induced deletion in mice, dual Hdac1 and Hdac2 deletion alters intestinal epithelial cell (IEC) growth and differentiation, leading to chronic colonic inflammation. In addition, in contrast to single Hdac1 or Hdac2 deletion, dual Hdac1 and Hdac2 deletion results in enteroid growth defects. Aims: Aims: In this work, we investigated whether Hdac1 or Hdac2 modify IEC-specific gene and protein expression programs, as well as differentiation pathways, in enteroids through common and/or different pathways. Methods: Methods: Jejunal villin-Cre Hdac1 or Hdac2 enteroids were grown in medium with or without SILAC, for proteome quantification by mass spectrometry. The transcriptome was assessed by RNA-Seq. Top Canonical Pathways were identified by IPA bioinformatics analysis. The phenotype of Hdac1 - and Hdac2 -deleted enteroids was determined by 1) microscopy; 2) HDAC activity measurements; 3) Alcian blue (goblet cells) and Best Carmine (Paneth cells) staining, 4) γ-H2AX immunohistochemistry, and 5) qPCR or Western blot analysis of selected differentiation markers, or HDAC1- or HDAC2-specific targets identified by RNA-Seq. Results: Results: Transcriptomic analysis revealed shared (FXR/RXR activation) and distinct (LXR/RXR activation, HDAC1; Retinoate biosynthesis, HDAC2) Top Canonical Pathways. Proteomic analysis revealed common (LPS/IL-1 mediated inhibition of RXR function) and different (Fatty acid oxidation, HDAC1; Aryl hydrocarbon receptor signaling, HDAC2) Top Canonical Pathways, among others. HDAC activity was slightly decreased in Hdac1 - or Hdac2 -deleted enteroids. Increased DNA damage was observed, as assessed by γ-H2AX staining. Both Hdac1 - or Hdac2 -deleted enteroids displayed augmented bud numbers, as well as increased numbers of goblet and intermediate cells, as determined by Alcian blue and Best Carmine staining. This correlated with increased expression of differentiation markers. qPCR analysis uncovered metabolic and inflammatory genes commonly regulated by HDAC1 and HDAC2 ( Nox1, Il18, Hmgcs2 ) or specifically regulated by HDAC1 ( St3gal4 ) or HDAC2 ( Muc3 ). Conclusions: Conclusion: HDAC1 and HDAC2 independently regulate enteroid differentiation and behavior by common and select pathways. In addition, HDAC1 and HDAC2 may selectively regulate IEC-intrinsic metabolic and environmental responses through a subset of differentially regulated genes dependent on their action. Selective pharmacological inhibition of HDAC1 or HDAC2 activity could be advantageous to control altered metabolic and inflammatory pathways in IEC and in the intestinal environment. Funding Agencies: CCC